Transcriptome analysis reveals the high ribosomal inhibitory action of 1,4-naphthoquinone on Meloidogyne luci infective second-stage juveniles - Cardoso, Joana M. S.; Esteves, Ivânia; Egas, Conceição; Braga, Mara E. M.; de Sousa, Hermínio C.; Abrantes, Isabel; Maleita, Carla (Frontiers in Plant Science, 2023)
The root-knot nematode (RKN) Meloidogyne luci presents a threat to the production of several important crops. This nematode species was added to the European Plant Protection Organization Alert list in 2017. The scarce availability of efficient nematicides to control RKN and the phasing out of nematicides from the market has intensified the search for alternatives, such as phytochemicals with bionematicidal properties. The nematicidal activity of 1,4-naphthoquinone (1,4-NTQ) against M. luci has been demonstrated, however knowledge of the potential mode(s) of action of this compound is still scarce. In this study, the transcriptome profile of M. luci second-stage juveniles (J2), the infective stage, in response to 1,4-NTQ exposure was determined by RNA-seq to identify genes and pathways that might be involved on 1,4-NTQ mode(s) of action. Control treatments, consisting of nematodes exposed to Tween® 80 (1,4-NTQ solvent) and to water, were included in the analysis. A large set of differentially expressed genes (DEGs) were found among the three tested conditions and a high number of down-regulated genes was found between 1,4-NTQ treatment and water control, reflecting the inhibitory effect of this compound on M. luci, with a great impact on processes related to translation (ribosome pathway). Several other nematode gene networks and metabolic pathways affected by 1,4-NTQ were also identified, clarifying the possible mode of action of this promising bionematicide.